2010
DOI: 10.21273/horttech.20.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Biocontainers for Greenhouse Crops Production

Abstract: The vertical dry strength of rice hull containers was the highest of all containers tested. Plastic containers and paper containers had similar vertical dry strengths. Containers composed of 80% cedar fiber and 20% peat (Fertil), composted dairy manure (Cowpot), and peat had lower dry vertical dry strengths than the aforementioned containers but had higher vertical dry strengths than those composed of bioplastic (OP47), coconut fiber, and rice straw. Rice hull containers and paper containers had the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 4 publications
5
82
2
Order By: Relevance
“…Recently, physical properties of several types of biodegradable pots such as rice-hull based pots and containers have been evaluated (Evans et al, 2010). These reports indicated that plants were grown successfully in media containing up to 30% feather fiber (Evans, 2004;Evans and Hensley, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, physical properties of several types of biodegradable pots such as rice-hull based pots and containers have been evaluated (Evans et al, 2010). These reports indicated that plants were grown successfully in media containing up to 30% feather fiber (Evans, 2004;Evans and Hensley, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, physical properties of several types of biodegradable pots such as rice-hull based pots and containers have been evaluated (Evans et al, 2010). These reports indicated that plants were grown successfully in the media containing up to 30% feather fiber (Evans, 2004;Evans and Hensley, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, obtaining biodegradable nutritive pots is based on the principles of sustainable development, considering the entire life cycle of the product [22]:…”
Section: Generation Development and Modifications Of Natural Fibersmentioning
confidence: 99%
“…Recently, alternative containers based on natural raw materials, impregnated with various components, such as slow-releasing fertilizers, fungicides, insecticides, and plant growth regulators that are released during plant growth, are gaining entry to the market and could enhance the efficiency of the production system. Industry and researchers are continuously working together to develop and fine-tune sustainable alternative containers to suit emerging grower and customer requirements [6,7].…”
Section: Introductionmentioning
confidence: 99%